Obesity in the pregnant diabetic population and delivery outcomes. (7th June 2011) - Oniya, O; Gallagher, A; Mackay, V; Gibson, J
Abstract : Introduction: Diabetes is the most common pre-existing medical condition in pregnancy in the UK. The global obesity epidemic has led to an increase in the incidence of Type 2 Diabetes in pregnancy and gestational diabetes. Obesity may also affect susceptibility to Type 1 Diabetes.1 Children of diabetic mothers are in turn pre-disposed to Type 2 Diabetes in adult life.2 Objective: To determine the prevalence of obesity in diabetics and correlate body mass index (BMI) with pregnancy outcomes. Results: 103 cases were identified. Age range was 15 to 43 years. Gestational diabetes n=45, Type 1 Diabetes n=50 and Type 2 Diabetes n=8. BMI was not recorded in 10 cases. BMI range 22–54. 67% were clinically obese. (Class 1 obesity=30%, Class 2 obesity=23% and Class 3 obesity=14%). 20.4% were overweight. Only 12.6% had BMI of 25 or less. In the Obese group the caesarean section rate was 57% (30% Elective and 27% Emergency). Spontaneous vaginal delivery rate was 31% and 12% had assisted vaginal delivery compared to a caesarean section rate of 50%, Vaginal delivery rate of 38.2% and assisted vaginal delivery rate of 11.8% in the non-obese group. 8% of all babies had intra uterine growth restriction. 45% were normal centile for gestation and 47% were above the 95th centile. (Range 1.7–5.4 kg). Conclusion: Obesity is strongly associated with both pre-existing and gestational diabetes in pregnancy. It appears to confer an even greater risk of operative delivery. A significant proportion of babies were macrosomic.